2021
DOI: 10.1192/j.eurpsy.2021.895
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in mood symptoms, cognitive symptoms and functioning in outpatients with mdd in greece treated with vortioxetine: A patient-rated evaluation

Abstract: IntroductionFunctional recovery is the contemporary treatment goal in Major Depressive Disorder (MDD). Although consistency among physician and patient expectations may influence the therapeutic result (Demyttenaere K et al, 2011), patients’ perceptions are not always fully captured. Vortioxetine,a multimodal antidepressant, has shown encouraging data in achieving functional recovery, improving both mood and cognitive symptoms (Mahableshwarkar AR et al, 2015).ObjectivesThe aim of the study was to assess the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
0
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
2
0
0
2
Order By: Relevance
“…Similarly, a meta-analysis of data from nine short-term randomized placebo-controlled clinical trials of vortioxetine 5–20 mg found overall functioning to be significantly improved in patients with MDD treated with vortioxetine, with greatest effects seen at a dosage of 20 mg/day ( 50 ). The observed improvement in cognitive symptoms during treatment with vortioxetine in the present study is also consistent with previous findings both in open-label studies ( 16 , 50 53 ) and randomized controlled clinical trials ( 24 , 54 58 ). It seems reasonable to assume that the observed improvement in functioning seen in patients with MDD during treatment with vortioxetine may at least in part be due to the beneficial effect of treatment on cognitive symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, a meta-analysis of data from nine short-term randomized placebo-controlled clinical trials of vortioxetine 5–20 mg found overall functioning to be significantly improved in patients with MDD treated with vortioxetine, with greatest effects seen at a dosage of 20 mg/day ( 50 ). The observed improvement in cognitive symptoms during treatment with vortioxetine in the present study is also consistent with previous findings both in open-label studies ( 16 , 50 53 ) and randomized controlled clinical trials ( 24 , 54 58 ). It seems reasonable to assume that the observed improvement in functioning seen in patients with MDD during treatment with vortioxetine may at least in part be due to the beneficial effect of treatment on cognitive symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this large international study are in keeping with those of other small-scale studies in patients with MDD treated with vortioxetine in routine care settings ( 16 , 50 53 ). Similarly, a meta-analysis of data from nine short-term randomized placebo-controlled clinical trials of vortioxetine 5–20 mg found overall functioning to be significantly improved in patients with MDD treated with vortioxetine, with greatest effects seen at a dosage of 20 mg/day ( 50 ).…”
Section: Discussionsupporting
confidence: 86%
“…В целом, результаты этого масштабного исследования согласуются с результатами имеющихся небольших исследований лечения БДР вортиоксетином в рутинной практике [13,18,19,30]. Аналогично, метаанализ данных девяти краткосрочных РКИ выявил улучшение общего функционирования пациентов с БДР, получавших лечение вортиоксетином в дозе 5-20 мг/сут, причем наибольший эффект наблюдался при применении препарата в дозе 20 мг/сут [12].…”
Section: Guidelines For the Practitioner в помощь практикующему врачуunclassified
“…Прокогнитивное действие вортиоксетина, продемонстрированное в настоящем исследовании, согласуется с результатами многочисленных РКИ и открытых исследований [13,18,19,30].…”
Section: Guidelines For the Practitioner в помощь практикующему врачуunclassified